2020
DOI: 10.1186/s40168-020-00892-z
|View full text |Cite
|
Sign up to set email alerts
|

Bio-organic fertilizers stimulate indigenous soil Pseudomonas populations to enhance plant disease suppression

Abstract: Background Plant diseases caused by fungal pathogen result in a substantial economic impact on the global food and fruit industry. Application of organic fertilizers supplemented with biocontrol microorganisms (i.e. bioorganic fertilizers) has been shown to improve resistance against plant pathogens at least in part due to impacts on the structure and function of the resident soil microbiome. However, it remains unclear whether such improvements are driven by the specific action of microbial inoculants, microb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(128 citation statements)
references
References 84 publications
(116 reference statements)
9
117
0
2
Order By: Relevance
“…Considering that, varying C compound and nutrient components tend to influence the microbial community [67,68], further fluctuations in community compositions are due to the contrasting chemical composition of the used fertilizers amendments. Recent findings by Tao et al [69] support increase of Pseudomonas in VTLW treatment, as authors reported that bioorganic fertilizers tend to increase indigenous Pseudomonas. Cyanobacteria abundance tends to increase in the optimal combination of biogenic elements in soil, such as reduced nitrogen content under a sufficient amount of phosphorus [60], which could underpin the higher abundance of these bacteria in PT treatment, which contain higher phosphorus.…”
Section: Discussionmentioning
confidence: 84%
“…Considering that, varying C compound and nutrient components tend to influence the microbial community [67,68], further fluctuations in community compositions are due to the contrasting chemical composition of the used fertilizers amendments. Recent findings by Tao et al [69] support increase of Pseudomonas in VTLW treatment, as authors reported that bioorganic fertilizers tend to increase indigenous Pseudomonas. Cyanobacteria abundance tends to increase in the optimal combination of biogenic elements in soil, such as reduced nitrogen content under a sufficient amount of phosphorus [60], which could underpin the higher abundance of these bacteria in PT treatment, which contain higher phosphorus.…”
Section: Discussionmentioning
confidence: 84%
“…Although decades of research have been carried out on banana Fusarium wilt, there are few effective control methods for this disease, and the breeding of disease-resistant varieties is the most effective management strategy ( Tao et al, 2020 ). However, these kinds of biological resources are usually scarce, unproductive, and commercially unacceptable ( Dita et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a continuation, Bonanomi et al [21] demonstrated that organic amendments with high labile C fractions would be conducive to plant damping-off disease in short-term but, became suppressive after 100-300 days of application. Recently, Tao et al [204] showed that the addition of bio-organic fertilizer shielded plants from pathogen infection increasing synergistic formation of biofilm at the root-microbiome interface, which may act as a plant-beneficial consortium against the soil-borne phytopathogens. An overall depiction of animal waste recycling and their reuse in farming systems to intensify agricultural productivity is reflected in Figure 2.…”
Section: Disease Suppressionmentioning
confidence: 99%